Analyzing the correlation between psychological capital in community nurses and their stress management and job satisfaction - Mostafa Shaban; Marwa Mamdouh Shaban; Huda Hamdy Mohammed; Majed Awad Alanazi; Hend Reda Ali Elkest (BMC Nursing)
Abstract Background Community nursing is marked by high stress due to direct patient interactions and varied work environments. Research highlights the significant role of psychological capital (PsyCap), which includes self-efficacy, hope, optimism, and resilience, in managing occupational stress and enhancing job satisfaction among health professionals. Objective This study examines the associations between Psychological Capital, stress management, and job satisfaction among community nurses, exploring their collective impact on professional well-being. Methods We employed a cross-sectional, correlational design with a convenience sampling method, recruiting 148 community nurses from Tanta University Educational Hospitals. The Compound Psychological Capital Scale (CPC-12), the Coping Orientation to Problems Experienced Inventory (Brief-COPE), and the Generic Job Satisfaction Scale (GJSS) were used for data collection. Pearson’s correlation and multiple regression analyses assessed the relationships and predictive values among the variables. Results The study demonstrated significant positive correlations between PsyCap and job satisfaction (r = .44, p < .001) and between PsyCap and stress management (r = .39, p < .01). Multiple regression analysis showed that PsyCap accounted for 29% of the variance in job satisfaction and 26% in stress management effectiveness. Self-efficacy, hope, and optimism were significant predictors of job satisfaction, with self-efficacy showing the strongest association (β = 0.33, p = .007). Conclusion Psychological Capital is associated with stress management and job satisfaction among community nurses, underscoring its importance in enhancing nurse coping mechanisms, reducing occupational stress, and improving job satisfaction. Practical implications include implementing training programs, resilience workshops, and mentorship initiatives to strengthen Psychological Capital among nurses, thereby improving workforce well-being and retention. Clinical trial number Not applicable.